PENGEMBANGAN KOMPETENSI PROFESIONAL KONSELOR DALAM LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH - rohima, Tila; syukur, yarmis; Sukma, Dina (Institut Syekh Abdul Halim Hasan Binjai, 2024)
The professional competence of counselors is an important aspect that must be considered in efforts to improve the quality of guidance and counseling services in schools. This research aims to identify and analyze strategies for developing counselors' professional competence in providing guidance and counseling services in schools. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation and documentation studies. Research participants consisted of school counselors, principals, and students at several high schools in certain areas. The research results show that the development of counselors' professional competence can be achieved through various strategies, including regular training and workshops, supervision and mentoring, as well as participation in professional communities of practice. Apart from that, support from school management and supportive educational policies also play an important role in developing these competencies. This research concludes that to improve the professional competence of counselors, a holistic and sustainable approach is needed, which involves various stakeholders in the educational environment. The findings from this research are expected to contribute to more effective training development programs and policies to improve the quality of guidance and counseling services at school. The practical implications of this research also include recommendations for counselors, school management, and policy makers to work together to create an environment that supports counselors' professional development.